Management of women affected by endometriosis: Are we stepping forward?. Issue 2 (June 2019) - Di Guardo, Federica; Shah, Mohsin; Cerana, Maria Cecilia; Biondi, Antonio; Karaman, Erbil; Török, Péter; Yela, Daniela A.; Giampaolino, Pierluigi; Marín-Buck, Alejandro; Laganà, Antonio Simone
Endometriosis is an estrogen-dependent chronic disease defined by the presence of endometrial-like tissue, glands and stroma in ectopic areas. Among all the pathogenic theories proposed to explain the origin of the disease, a pivotal role for immune, hormonal, and epigenetic disbalances have been hypothesized. Endometriosis affects up to 10%–15% of women in reproductive age and represents one of the most common gynecological causes of severe pelvic pain. The main symptoms reported by patients are dysmenorrhea and deep dyspareunia. Although the histological confirmation has been commonly considered mandatory, to date the possibility offered by the improvement in imagining techniques allows to make a proper diagnosis of the disease in most of the cases. Medical therapy represents only a symptomatic treatment and not the definitive solution. The aim of the hormonal therapy is to abolish the menstrual flow using progestin, oral contraceptives, and gonadotropin-releasing hormone agonists to reduce pelvic pain. Surgical treatment consisting of laparoscopy has the goal of abolishing pain and may be conservative or radical in nature depending on the patients' desire of spontaneous conception in the future. Radical surgery seems to be associated with a higher percentage of pain relief as well as higher recurrence rates. Due to the worldwide acceptance and the ongoing evolution of minimally invasive surgery to treat both benign and malignant diseases, future investigations may be conducted to consider this approach to save the function of all the organs involved by the disease and to reduce post-operative discomfort and psychological impact.